The taxonomic status of Deroceras hesperium Pilsbry, 1944 (Gastropoda: Pulmonata: Agriolimacidae), a species of conservation concern in Oregon, USA - Roth, Barry; Jadin, Robert; Jadin, Robert (Zootaxa, 2013)
Two native species of the slug genus Deroceras Rafinesque, 1820, have been identified in samples from Fremont–Winema National Forest and other national forests in the Pacific Northwest of the United States: (a) Deroceras laeve (Müller, 1774), common and widespread in North America (Pilsbry, 1948); and (b) Deroceras hesperium Pilsbry, 1944, thought to have a more restricted distribution and considered a species of special status by the US Forest Service and US Bureau of Land Management. Since at least 2004 the two species have been identified in previous samples on the basis of external appearance and features of the reproductive system. The localities for the two species are distributed in a mosaic, seemingly haphazard, pattern within the forests. Most samples previously examined and identified by author BR were assignable in toto to one or the other species, but both D. hesperium and D. laeve were identified in a sample from John Spring, Klamath County, Oregon. Specimens from central and southern Oregon counties represented an extension of the published range of D. hesperium southward from Oswego Lake, Clackamas County (Pilsbry, 1948; Branson, 1977).